Analisis Perbandingan Performa Saat Takeoff Pada Engine CFM56-7b Dengan Konfigurasi Thrust Rating 26300 Lbs Dan 27300 Lbs - Setiyawati, Defi; Alimin, Edy K.; Yuniarti, Endah (Jurnal Teknologi Kedirgantaraan, 2022)
The CFM 56-7B engine is manufactured by CFM International which is used on the B737-600/700/800/900 aircraft. This engine has several variations of the thrust rating with varying performance. Engine performance parameters include Thrust, Specific Fuel Consumption (SFC), Core Speed (N2), and Exhaust Gas Temperature (EGT). Performance testing can be done using the Engine Test Cell. However, the engine test cell is a calibrated tool, which allows deviation of the test results. Then the performance calculation is done using the formula in the Engine Shop Manual - Test 003 - Engine Acceptance Test to find out the engine performance during the takeoff phase at the highest thrust rating of 26300 lbs and 27300 lbs and compare the performance of the two engines. Comparison of the calculation results states that an engine with a thrust rating of 26300 lbs is superior to Exhaust Gas Temperature, while an engine with a thrust rating of 27300 lbs has advantages at Thrust, Specific Fuel Consumption and Core Speed (N2).